Transformational leadership, athletes' satisfaction and sport commitment: a study of Iranian high school football teams - Saybani, H. R.; Yusof, Aminuddin; Soon, C.; Hassan, A.; Zardoshtian, S. (VictorQuest Publications, 2013)
The aim of this study is to investigate the relationship between transformational leadership style of Iranian high schools’ coaches, sport commitment and athletes’ satisfaction of Iranian high schools’ football players. The survey design, correlational study, and inferential statistics were applied in this research. The SEM was applied as a strong procedure to analyze the data and to develop the models. This study conducted in Alborz province of Iran. Population of this study was 558 football players (15-20 years), participating in an annual tournament that is organized by the Ministry of Education’s sport department of Iran. A total of 280 high schools’ football players were selected to participate in this study by using the simple random sampling procedure. Instruments of the study were MLQ (Bass & Avolio, 1995), SCMS (Scanlan, et al., 1993) and ASQ (Riemer & Chelladurai, 1998). The results of the study indicated that there is a positive and significant relationship between transformational leadership style of coaches, sport commitment (r = .419, β =.478, ρ value=.001), and athlete satisfaction of football players(r = .386, β =.443, ρ value=.001). Therefore, it can be concluded that transformational leadership behaviors can increase sport commitment and athletic satisfaction of high schools’ football players. Structural model was fit the data of the current study.